José Martí: entierros y desentierros. - Fragoso González, Oraldo Antonio; Macías Pérez, Jorge Luis; Fragoso Vega, Oraldo; Cedeño Morales, Raúl (Revista 16 de abril, 2017)
On May 19, 1895, José Martí died mortally wounded; the remains of it were buried and exhumed several times. In total, there are five times that it was buried in the most diverse places, from Remanganagua, on May 20, 1895, to the José Martí Mausoleum, where the mortal remains of the same place lie. The objective of this work was to analyze the burials and unearthings of the Master after his fall in combat, and in the long pilgrimage to his final bed. The analysis and synthesis and logical historical methods were used for its preparation, with a total of 12 bibliographical references.